Effects of a structured nutrition literacy enhancement program on the knowledge, skills, and dietary behaviors of village health volunteers in Rural Thailand: Single-group repeated-measures evaluation - Somhwang Sakunsenanarong; Yada Boonma; Wiranphat Somsut; Natsuda Chumcharoen; Krich Ruangchai; Apinya Uttrachai (Journal of Public Health and Development, 2026)
Non-communicable diseases represent Thailand's predominant health challenge, with nutrition-related factors critically influencing disease prevention. Village health volunteers (VHVs) serve as essential healthcare intermediaries connecting Thailand's primary care system to rural communities but demonstrate insufficient nutrition literacy competencies. This single-group repeated-measures study evaluated a structured 12-week nutrition literacy enhancement program among 35 VHVs in rural Thailand from July to October 2024. The intervention comprised interactive workshops, peer learning sessions, and community-based activities grounded in Social Cognitive Theory and Adult Learning Theory. Validated instruments assessed three nutrition literacy domains (functional, interactive/communicative, and critical), nutrition knowledge, and dietary behaviors at baseline and weeks 4, 8, 12, and 16. Linear mixed-effects models with random intercepts and AR(1) covariance structures were used to analyze trajectories. Significant improvements occurred across all domains: Knowledge increased 60.3% (β=0.52, 95%CI: 0.48-0.56, p